EFFECT OF STRUCTURED EXERCISE REGIMEN ON QUALITY OF LIFE, BALANCE AND STRENGTH ON A PATIENT WITH MIYOSHI MYOPATHY – A CASE REPORT (International Journal of Physiotherapy, 2020)
Background: Dysferlinopathy is an autosomal recessive disease seen in adolescence or young adulthood. Miyoshi Myopathy is characterized by weakness and wasting of posterior compartment leg muscles rather than the anterior compartment and distal upper limb muscles. Still, the intrinsic muscles of the foot and hands are spared. There are several undiagnosed cases in India and also around the world with dysferlinopathy. Diagnosis for the same requires advanced biological laboratories along with high economic funding for diagnostic purposes.Case Summary: This case report presents a 22-year-old male diagnosed with Miyoshi myopathy/LGMD2b(dysferlinopathy). The subject complained about a loss of balance, strength, and difficulty in performing activities of daily living. The patient was given Aquatic Therapy along with conventional physical therapy for a duration of 6weeks, which included three days of supervised therapy along with 3days home protocol and a rest day kept at the end of every week.Outcome Measures: Standardized scales like the Barthel Index and the Berg Balance Scale were used for the assessment of pre and post the progress of the subject for Quality of Life and Balance, respectively. Manual Muscle testing was used for assessments for pre and post muscle strength of the subject.Conclusion: The timely diagnosis of a rare condition before the advancement of the disorder and thus the use of appropriate intervention of physiotherapy, which consisted of progressive muscle-strengthening exercises along with balance training proved to be promising in preventing falls, muscle atrophy and thus making the patient independent for doing daily activities.